Mastering Linux security and hardening secure your Linux server and protect it from intruders, malware attacks, and other external threats - Tevault, Donald A. (Packt Publishing, 2018)
The author presents a guide to mastering the art of preventing Linux systems from getting compromised. Learn how to perform a number of advanced Linux security techniques such as network service detection, user authentication, controlling special permissions, encrypting file systems, and more. This book has coverage of techniques that will help prevent attackers from breaching systems, covering topics such as SSH hardening, network service detection, setting up firewalls, encrypting file systems, and protecting user accounts.